Anthropological Perspectives on Care - Alber, Erdmute. author. aut Link
X, 237 p.
Keywords: In the course of last two decades, the notion of care has become prominent in the social and cultural sciences. As a result of this proliferation of care in several disciplinary fields, we are observing not only the expansion of its conceptual meaning, but also an increasing imprecision in its usage. A growing amount of literature focuses on the intersection between work, gender, ethnicity, affect, and mobility regimes. In view of this growing field of literature, Anthropological Perspectives on Care looks at the notion of care from an anthropological perspective. Complementing earlier approaches, Alber and Drotbohm argue that an interpretation of care in relation to three different concepts, namely work, kinship and the life-course, will facilitate empirical and conceptual distinctions between the different activities that are labeled as care.